KRIM KULIT BUAH DURIAN (Durio zibethinus L.) SEBAGAI OBAT HERBAL PENGOBATAN INFEKSI JAMUR Candida albicans - Hanny Setyowati; Hananun Zharfa Hanifah; Rr Putri Nugraheni; Wahyuning Setyani (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Durian rind (Durio zibethinus L.) is a part of plant reported to have antifungal activity toward Candida albicans fungi. This research aimed to make extract rind of D. zibethinus L. formula cream and evaluated the physical characteristic toward C. albicans. The formulation of extract rind of D. zibethinus L. is made based on preliminary test with variety of extract concentration, which is 15%, 20%, and 25%. Negative control used basis cream consisting of emulgide, paraffinum liquidum, and aquadest, whereas positive control used Ketoconazole 2%. Cream produced was further tested for: organoleptic,homogeneity, adhesive power, dispersive power, and protection power. Antifungal activity tested is done by diffusion method. Antifungal activities data are analyzed by one way ANOVA. The result of this research showed that extract rind of D. zibethinus L. contains saponin, flavonoid, and tannin which is the formulation in cream had antifungal activities towards C. albicans with average resistibility zone diameter for 15% (0,62 cm) extract concentration, 20% (0,73 cm) extract concentration, and 25% (0,81 cm) extract concentration.